2006
DOI: 10.1042/bj20060655
|View full text |Cite
|
Sign up to set email alerts
|

Statins inhibit the dimerization of β-secretase via both isoprenoid- and cholesterol-mediated mechanisms

Abstract: We have previously reported that protein lipidation in the form of palmitoylation and farnesylation is critical for the production of Abeta (amyloid beta-peptide), the dimerization of beta-secretase and its trafficking into cholesterol-rich microdomains. As statins influence these lipid modifications in addition to their effects on cholesterol biosynthesis, we have investigated the effects of lovastatin and SIMVA (simvastatin) at a range of concentrations chosen to distinguish different cellular effects on Abe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
73
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 44 publications
(101 reference statements)
9
73
0
Order By: Relevance
“…Initial studies demonstrated that lowering of membrane cholesterol by statins results in decreased generation of A␤ by altering the subcellular transport, localization, and dimerization of either APP, secretases, or both (47)(48)(49)(50). Recent studies also support a predominant role of protein isoprenylation in the statin-mediated effects on APP processing and plaque pathology (16,17,19). However, there are also data indicating the lack of any positive effects of statins on A␤ levels, amyloid pathology, and Tau metabolism.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Initial studies demonstrated that lowering of membrane cholesterol by statins results in decreased generation of A␤ by altering the subcellular transport, localization, and dimerization of either APP, secretases, or both (47)(48)(49)(50). Recent studies also support a predominant role of protein isoprenylation in the statin-mediated effects on APP processing and plaque pathology (16,17,19). However, there are also data indicating the lack of any positive effects of statins on A␤ levels, amyloid pathology, and Tau metabolism.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to inhibition of cholesterol biosynthesis, statins also impair the generation of isoprenoids, including farnesyl pyrophosphate (FPP) and geranylgeranyl pyrophosphate that play important roles in the post-translational modifications of Rho and Rab proteins thereby regulating their localization and biological function. Isoprenoids have also been shown to affect A␤ generation, by modulating ␤-secretase as well as ␥-secretase cleavage of APP (16,17,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although statins affect A␤ metabolism, their proposed mechanism of action on A␤ production is quite diverse as follows: up-regulation of ␣-secretase processing, down-regulation of ␤-secretase processing, down-regulation of ␥-secretase processing, modulation of APP trafficking, and up-regulation of APP-CTF degradation (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). However, it should be noted that these various mechanisms were demonstrated mostly by in vitro studies.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…A reduction in -secretase activity is also reported to be involved in amyloid processing disturbances triggered by statins. Work by Parsons et al, 2006, showed that statins may interfere with the dimerization of -secretase thus, lowering its activity and reducing the amounts of A produced. However, a linear dose-response was not observed.…”
Section: Role Of Statins In Admentioning
confidence: 99%